Legal regulation of electronic payment via mobile phone wallet (Eurasian Journal of Humanities and Social Sciences, 2025)
To improve the services provided to the consumer and benefit from data in reducing the cost of payments, modern innovations appeared around the electronic wallet via mobile phone in 2007, after the method depended on electronic plastic and magnetic cards in ecommerce, which were practiced in the form of traditional money transfers at the beginning of the emergence of e-commerce, and this tangible development did not produce development in the laws controlling and rulings for dealing with electronic wallets, and this rapid technological development also requires development in the laws that regulate it, otherwise it will not gain legal legitimacy during its commercial and civil transactions, so it is necessary to stand on the legal regulation of electronic payment via the mobile phone wallet.